A bioceramic gutta-percha point and a method for preparing the same
By using the method of esterified chitosan loaded with nano-zinc oxide and allyl gallic acid to modify ceramic powder, the antibacterial and sealing properties of bioceramic gutta-percha tips were improved, the problems of microleakage and insufficient antibacterial properties were solved, and a gutta-percha tip material with high sealing and developing effects was achieved.
Patent Information
- Application Number
- CN202510190023.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-02-20
AI Technical Summary
Existing bioceramic gutta-percha tips have deficiencies in microleakage and antibacterial properties, which affect the treatment effect and sealing performance.
Esterified chitosan was prepared by reacting glutathione with chitosan, and nano-zinc oxide was prepared by hydrothermal synthesis and loaded with esterified chitosan to enhance antibacterial properties. Ceramic powder was modified with allyl gallic acid to improve dispersibility and biocompatibility, and the compatibility of natural rubber and filling paste was combined to enhance the sealing and angiographic effects.
The prepared bioceramic gutta-percha tip has good biocompatibility, antibacterial properties and appropriate bending strength, high sealing performance, reduced microleakage, and improved treatment comfort and visualization effect.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of gutta-percha points, in particular to a bioceramic gutta-percha point and a preparation method thereof. BACKGROUND
[0002] With the improvement of economic level and living conditions, people's oral health care consciousness also improves, oral health not only determines our quality of life, but also is regarded as the first barrier of human health, and is an important guarantee for healthy life. People pay attention to tooth damage, dental caries, periodontitis and other dental problems caused by some bad habits. In order to remove the infection inside the tooth and prevent the infection from further spreading, root canal treatment is one of the common means to protect the structure of the tooth and avoid tooth extraction. Gutta-percha point is a commonly used medical instrument in root canal treatment. When filling the root canal, the gap between the gutta-percha point and the root canal wall is filled with paste to improve the sealing effect of the root canal. Therefore, the research and development of gutta-percha point material has become the focus of the personnel in this field.
[0003] Patent CN114099351A discloses a bioceramic gutta-percha point. The gutta-percha point includes components: natural rubber, zinc oxide, barium sulfate, zirconium oxide, silicon dioxide, antioxidant, bioactive material and pigment. The bioceramic gutta-percha point has good biocompatibility, solves the micro-gap and micro-leakage phenomenon between the gutta-percha point and the filling paste, improves the developing effect, and increases the brightness by 20%. It has the function of inducing bone regeneration and has no toxic side effects, but the addition of pigment may stimulate the gums and affect the treatment effect.
[0004] Patent CN118078641A discloses a hydrophilic root canal filling point material and a preparation method thereof. The hydrophilic root canal filling point material prepared by using thermoplastic polymer material and introducing hydrophilic additives has good swelling performance and biocompatibility, and can completely eliminate the micro-gap and micro-leakage phenomenon of traditional root canal materials. Modified antibacterial agent is added, and halloysite nanotubes, thymol, sodium alginate and trehalose are mixed respectively. The four can form a carrier system with synergistic effect. Halloysite nanotubes can effectively load thymol, and through the synergistic effect of sodium alginate and trehalose, the stability and bioavailability are increased, thereby improving the antibacterial property and antioxidant property of the prepared hydrophilic root canal filling point material. However, the prepared material of the invention has not been studied for micro-leakage, which is one of the important indicators for judging the performance of the filling material.
[0005] Therefore, there is an urgent need in the market for a bioceramic gutta-percha point with good treatment effect and good sealing property. SUMMARY
[0006] In view of the problems in the prior art, the purpose of the present application is to obtain a bioceramic gutta-percha point with good biocompatibility and antibacterial property, suitable bending strength for easy treatment, and a contrast effect.
[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present application is as follows:
[0008] In one aspect, the present application provides a bioceramic gutta-percha point, which comprises the following raw materials in parts by weight: natural rubber 10-20 parts, antibacterial agent 30-40 parts, barium sulfate 8-12 parts, modified ceramic powder 8-15 parts, and plasticizer 2-3 parts.
[0009] In some embodiments, the preparation method of the antibacterial agent comprises the following steps:
[0010] 1) Glutathione and chitosan are added to DMSO, and a sulfuric acid solution is added, and reacted at 70-80℃ for 7-8h, filtered, washed, and dried to obtain esterified chitosan;
[0011] 2) A 0.05-0.06mol / L zinc acetate anhydrous ethanol solution is stirred at 40-50℃ for 50-70min, then 0.08-0.09mol / L sodium hydroxide solution is added while stirring, and the esterified chitosan obtained in step 1) is added, and stirred at 40-50℃ for 1-2h, and then left to stand, filtered, washed, and dried to obtain the antibacterial agent.
[0012] Firstly, the present application utilizes the reaction of glutathione and chitosan to obtain esterified chitosan, and then utilizes a hydrothermal synthesis method to prepare nano-zinc oxide, and adds esterified chitosan during the preparation process, so as to load chitosan on the nano-zinc oxide, and obtain the antibacterial agent, which has good antibacterial property and sealing property. The possible reason is that the hydroxyl groups on the surface of the nano-zinc oxide loaded with chitosan are consumed, and the esterified chitosan with certain steric hindrance is also loaded, so that the surface energy is reduced, and the nano-zinc oxide is not easy to agglomerate, and is more uniform with the natural rubber. In addition, the esterified chitosan has certain softness and biocompatibility, which can avoid the problem of gap between the gutta-percha point and the paste due to loose connection. Furthermore, the amino groups of the esterified chitosan can be combined with zinc oxide, and the two can synergistically improve the antibacterial effect.
[0013] In some embodiments, the mass ratio of the glutathione to the chitosan in step 1) is (0.2-0.5):1.
[0014] In some embodiments, the mass ratio of the zinc acetate anhydrous ethanol solution to the esterified chitosan in step 2) is 1:(0.1-0.5).
[0015] The application limits the mass ratio of glutathione and chitosan, so that the grafting of glutathione on the surface of chitosan not only improves the dispersibility of the antibacterial agent, but also avoids the problem that the filling site is sensitive and the sealing property is reduced due to the excessive glutathione of the gutta-percha point. In addition, the limitation of the mass ratio of the zinc acetate anhydrous ethanol solution and the esterified chitosan improves the antibacterial property, while the mechanical property of the gutta-percha point is not affected.
[0016] In some embodiments, the method for preparing the modified ceramic powder comprises the following steps:
[0017] (1) Gallic acid and acrylic acid are added into dichloromethane, and a phosphoric acid solution is added, and stirring is performed at 70-80℃ for 7-8h, extraction, concentration, and drying are performed to obtain allylated gallic acid;
[0018] (2) The ceramic powder and KH570 are added into ethanol, and reaction is performed at 70-80℃ for 5-6h, and then the allylated gallic acid obtained in step (1) and azobisisobutyronitrile are added, and the reaction is continued for 1-2h to obtain the modified ceramic powder.
[0019] The addition of the ceramic powder and zirconia into the gutta-percha point can improve the toughness of the gutta-percha point, so that the gutta-percha point is not easy to break during use, and can better adapt to the shape of the tooth root canal, so as to achieve the effect of tightly filling the root canal, and can improve the developing effect of the gutta-percha point, but the dispersibility of the ceramic powder in the system is poor, and the mixture may not be uniform, which affects the toughness. The present application modifies the ceramic powder by using allylated gallic acid, which improves the dispersibility and biocompatibility of the ceramic powder, can reduce the microgap and microleakage phenomenon between the gutta-percha point and the filling paste, and can improve the contrast effect. The possible reason is that the increase of the hydroxyl and ester groups on the surface of the allylated gallic acid increases the interaction force and biocompatibility between the antibacterial agent, and the π-π interaction between the benzene ring structure and the double bond of natural rubber makes it easier to mix uniformly, and the compatibility between the filling paste is higher. Not only does it improve the filling property, but also improves the contrast effect. During the root canal treatment, the doctor can adjust the filling strategy according to the position of the gutta-percha point on the X-ray film to reduce the discomfort of the patient. In addition, the alkane chain segment increases the flowability of the gutta-percha point, so that it is easier to enter the inside of the root canal, and further improves the filling effect.
[0020] In some embodiments, the mass ratio of gallic acid to acrylic acid in step (1) is 1:(0.5-0.9).
[0021] In some embodiments, the mass ratio of the ceramic powder to the allylated gallic acid is 1:(0.2-0.6).
[0022] In some embodiments, the ceramic powder is a nano-sized zirconia ceramic powder, and the particle size is 30-50nm.
[0023] The application enhances the dispersibility of the ceramic powder and the flowability of the gutta-percha point by limiting the mass ratio of the ceramic powder to the allylated gallic acid after limiting the double bond of the allylated gallic acid to graft part of the gallic acid, and further limits the type and particle size of the ceramic powder to make it not only easier to fill, but also have a good imaging effect.
[0024] In some embodiments, the plasticizer is one or more of rosin, beeswax, or palm wax.
[0025] The second aspect of the application provides a preparation method of a bioceramic gutta-percha point, comprising the following steps: heating natural rubber at 80-100 DEG C for 1-2 hours, then adding an antibacterial agent, barium sulfate, modified ceramic powder and a plasticizer, heating to 100-110 DEG C and stirring for 55-65 minutes, then adding into a mold, cooling at room temperature to obtain the bioceramic gutta-percha point.
[0026] Compared with the prior art, the application has the following beneficial effects:
[0027] (1) The gutta-percha point prepared by the application has good biocompatibility and antibacterial properties, suitable bending strength, high comfort and high sealing property.
[0028] (2) The application first uses glutathione to react with chitosan to obtain esterified chitosan, and uses a hydrothermal synthesis method to prepare nano zinc oxide, and adds esterified chitosan in the preparation process to load chitosan on the nano zinc oxide, the hydroxyl groups on the surface of the nano zinc oxide loaded with chitosan are consumed, and the esterified chitosan with certain steric hindrance is loaded, the surface energy is reduced, the nano zinc oxide loaded with chitosan is not easy to agglomerate, and is more uniform with natural rubber, in addition, the esterified chitosan has certain softness and biocompatibility, which can avoid the problem of loose connection between the gutta-percha point and the paste, and in addition, the amino group of the esterified chitosan can be combined with zinc oxide, and the two synergistically improve the antibacterial effect.
[0029] (3) The application modifies the ceramic powder by using allylated gallic acid, the hydroxyl and ester groups on the surface of the allylated gallic acid increase the force and biocompatibility between the antibacterial agent, in addition, the π-π interaction between the benzene ring structure and the double bond of the natural rubber is more uniform, and the compatibility between the filling paste is higher, not only the filling property is improved, but also the imaging effect is improved, in the root canal treatment process, the doctor can adjust the filling strategy according to the position of the gutta-percha point on the X-ray film to reduce the discomfort of the patient, in addition, the alkane chain segment increases the flowability of the gutta-percha point, which makes it easier to enter the inside of the root canal, and further improves the filling effect. DETAILED DESCRIPTION
[0030] The present application will be described below in conjunction with specific embodiments. It should be noted that the following examples are for illustration of the present application and are not intended to limit the present application. Other combinations and various modifications within the concept of the present application can be made without departing from the spirit or scope of the present application.
[0031] In the following examples and comparative examples, the compounds and related reagents used are commercially available, wherein the natural rubber is model 3L rubber, purchased from Guangzhou Housheng New Material Co., Ltd.; the ceramic powder is nano-sized zirconia ceramic powder with a particle size of 40 nm, purchased from Hangzhou Jibin New Material Co., Ltd.; the beeswax is medicinal grade yellow beeswax, purchased from Xi'an Jinxiang Pharmaceutical Auxiliary Material Co., Ltd., and the ZOE paste is purchased from Shanghai Jinghua Chemical Factory.
[0032] Preparation Example 1
[0033] The preparation method of the antibacterial agent-1 includes the following steps:
[0034] 1) 4 g of glutathione and 10 g of chitosan are added into 100 ml of DMSO, and then 85 wt% sulfuric acid solution is added, and reacted at 75°C for 7.5 h, and then filtered, washed, and dried to obtain esterified chitosan;
[0035] 2) 10 g of 0.05 mol / L zinc acetate anhydrous ethanol solution is stirred at 45°C for 60 min, and then 0.08 mol / L sodium hydroxide solution is added while stirring, and 3 g of esterified chitosan obtained in step 1) is added, and stirred at 45°C for 1.5 h, and then left to stand, filtered, washed, and dried to obtain the antibacterial agent-1.
[0036] Preparation Example 2
[0037] The preparation method of the antibacterial agent-2 is the same as that of Preparation Example 1, except that the amount of glutathione added is 7 g.
[0038] Preparation Example 3
[0039] The preparation method of the antibacterial agent-3 is the same as that of Preparation Example 1, except that the amount of esterified chitosan added is 7 g.
[0040] Preparation Example 4
[0041] The preparation method of the antibacterial agent-4 includes the following steps: 10 g of 0.05 mol / L zinc acetate anhydrous ethanol solution is stirred at 45°C for 60 min, and then 0.08 mol / L sodium hydroxide solution is added while stirring, and stirred at 45°C for 1.5 h, and then left to stand, filtered, washed, and dried to obtain the antibacterial agent-4.
[0042] Preparation Example 5
[0043] The preparation method of the antibacterial agent-5 comprises the following steps: stirring 10 g of 0.05 mol / L zinc acetate anhydrous ethanol solution at 45°C for 60 min, then stirring while adding 0.08 mol / L sodium hydroxide solution, and adding 3 g of chitosan at the same time, stirring at 45°C for 1.5 h, standing, filtering, washing, and drying to obtain the antibacterial agent-5.
[0044] Preparation Example 6
[0045] The preparation method of the modified ceramic powder-1 comprises the following steps:
[0046] (1) 10 g of gallic acid and 7 g of acrylic acid are added into 100 ml of dichloromethane, and then 75 wt% phosphoric acid solution is added, stirring at 75°C for 7.5 h, extracting, concentrating, and drying to obtain allylated gallic acid;
[0047] (2) 10 g of zirconia ceramic powder and 5 g of KH570 are added into 100 ml of anhydrous ethanol, and then the reaction is carried out at 75°C for 5.5 h, 4 g of the allylated gallic acid obtained in step (1) and 0.1 g of azobisisobutyronitrile are further added, and the reaction is continued for 1.5 h to obtain the modified ceramic powder-1.
[0048] Preparation Example 7
[0049] The preparation method of the modified ceramic powder-2 is the same as that of the preparation example 5, except that the amount of acrylic acid added is 11 g.
[0050] Preparation Example 8
[0051] The preparation method of the modified ceramic powder-3 is the same as that of the preparation example 5, except that the amount of allylated gallic acid added is 8 g.
[0052] Example 1
[0053] A bioceramic gutta-percha point comprises the following raw materials in parts by weight: natural rubber 15 parts, antibacterial agent-1 35 parts, barium sulfate 10 parts, modified ceramic powder-1 12 parts, and beeswax 2.5 parts.
[0054] The preparation method of the bioceramic gutta-percha point of the present example comprises the following steps: the natural rubber is masticated at 90°C for 1.5 h, and then the antibacterial agent-1, barium sulfate, modified ceramic powder-1, and beeswax are added, and the temperature is raised to 105°C for stirring for 60 min, and then the mixture is added into a mold, and cooled at room temperature to obtain the bioceramic gutta-percha point.
[0055] Example 2
[0056] A bioceramic gutta-percha point comprises the following raw materials in parts by weight: natural rubber 10 parts, antibacterial agent-1 30 parts, barium sulfate 8 parts, modified ceramic powder-1 8 parts, and beeswax 2 parts.
[0057] The preparation method of the bioceramic gutta-percha point of the embodiment comprises the following steps: natural rubber is masticated at 80℃ for 2h, and then antibacterial agent-1, barium sulfate, modified ceramic powder-1 and beeswax are added, the temperature is raised to 100℃ and stirred for 65min, then the mixture is added into a mold and cooled at room temperature to obtain the bioceramic gutta-percha point.
[0058] Example 3
[0059] A bioceramic gutta-percha point comprises the following raw materials in parts by weight: natural rubber 20 parts, antibacterial agent-1 40 parts, barium sulfate 12 parts, modified ceramic powder-1 15 parts, and beeswax 3 parts.
[0060] The preparation method of the bioceramic gutta-percha point of the embodiment comprises the following steps: natural rubber is masticated at 100℃ for 1h, and then antibacterial agent-1, barium sulfate, modified ceramic powder-1 and beeswax are added, the temperature is raised to 110℃ and stirred for 55min, then the mixture is added into a mold and cooled at room temperature to obtain the bioceramic gutta-percha point.
[0061] Example 4
[0062] A bioceramic gutta-percha point and a preparation method thereof, the specific implementation manner is the same as that of example 1, and the difference lies in that antibacterial agent-1 is replaced by antibacterial agent-2 in equal amount.
[0063] Example 5
[0064] A bioceramic gutta-percha point and a preparation method thereof, the specific implementation manner is the same as that of example 1, and the difference lies in that antibacterial agent-1 is replaced by antibacterial agent-3 in equal amount.
[0065] Example 6
[0066] A bioceramic gutta-percha point and a preparation method thereof, the specific implementation manner is the same as that of example 1, and the difference lies in that antibacterial agent-1 is replaced by antibacterial agent-4 in equal amount.
[0067] Example 7
[0068] A bioceramic gutta-percha point and a preparation method thereof, the specific implementation manner is the same as that of example 1, and the difference lies in that antibacterial agent-1 is replaced by antibacterial agent-5 in equal amount.
[0069] Example 8
[0070] A bioceramic gutta-percha point and a preparation method thereof, the specific implementation manner is the same as that of example 1, and the difference lies in that modified ceramic powder-1 is replaced by modified ceramic powder-2 in equal amount.
[0071] Example 9
[0072] A bioceramic gutta-percha point and a preparation method thereof, the specific implementation manner is the same as that of example 1, and the difference lies in that the modified ceramic powder-1 is replaced by the modified ceramic powder-3 in equal amount.
[0073] Comparative example 1
[0074] A bioceramic gutta-percha point and a preparation method thereof, the specific implementation manner is the same as that of example 1, and the difference lies in that the modified ceramic powder-1 is replaced by the modified ceramic powder-3 in equal amount.
[0075] Performance test
[0076] 1. Bending strength
[0077] The bioceramic gutta-percha points prepared in the above examples and comparative examples are tested with reference to GB / T 9341-2021.
[0078] 2. Antibacterial property
[0079] The bioceramic gutta-percha points prepared in the above examples and comparative examples are subjected to antibacterial experiments with reference to GB / T 31402-2023.
[0080] 3. Cytotoxicity experiment
[0081] The gutta-percha points obtained in the examples and comparative examples are subjected to experiments with reference to GB / T 16886.5-2017 “Medical devices-Biological evaluation Part 5: In vitro cytotoxicity tests”, and none of them has cytotoxicity.
[0082] 4. Microleakage experiment
[0083] 4.1 Sample collection and preparation
[0084] Freshly extracted non-carious single-rooted anterior teeth of periodontal disease patients in the outpatient department of maxillofacial surgery of a certain oral hospital are collected, the teeth are placed in 5.25% sodium hypochlorite for 1 h, calculus and periodontal membrane are scraped off, and the teeth are cleaned and then soaked in physiological saline for standby. The teeth are opened and the pulp is removed; a No. 15 K file is used to open the root tip hole and determine the working length; the root canal is prepared by the step-back method, and 3wt% H2O2 and physiological saline are alternately flushed, and finally 5.25wt% sodium hypochlorite is used for flushing, and the root canal is dried with a paper tip. The prepared teeth are divided into groups, 30 teeth in each group, and the root canals are filled with ZOE paste and gutta-percha points, and the paste is uniformly coated on the inner wall of the root canal by rotating the paste counterclockwise with a No. 35 root canal file during paste filling. The root filling requires no overfilling or underfilling. After root filling, the crown is padded with zinc phosphate cement, and silver amalgam is filled.
[0085] 4.2 Experimental process
[0086] All samples were placed in airtight glass containers with sterile water cotton balls, and were placed in a 37℃ constant temperature box for 7 days. After the root filling material solidified, the samples were taken out, dried, and the root surface was evenly coated with 2 layers of nail polish 2mm above the root tip hole. After 24 hours of standing, the samples were immersed in a 2wt% methylene blue solution at 37℃ for 7 days. The samples were taken out, rinsed with running water, dried, and the nail polish was scraped off.
[0087] The teeth were made into transparent specimens using Robertson's technique. After the dye was washed out, the specimens were placed in 5wt% nitric acid (submerged specimens) for 72 hours, and the nitric acid solution was replaced every 24 hours. After rinsing with running water, the specimens were placed in an 80wt% alcohol solution for 12 hours, a 90wt% alcohol solution for 24 hours, and finally in anhydrous ethanol for 24 hours to dehydrate the specimens. The specimens were made transparent by placing them in wintergreen oil overnight. The length of dye penetration into the root canal wall of each specimen was measured under a root canal microscope at 40x magnification, and the average value of each group of samples was recorded.
[0088] The test results are shown in Table 1:
[0089] Table 1
[0090] Group Bending strength (MPa) Antibacterial rate (%) Average value (mm) Example 1 53.6 99 0.36 Example 2 48.7 96 0.47 Example 3 50.3 98 0.41 Example 4 58.9 97 0.98 Example 5 41.2 99 0.90 Example 6 46.2 91 0.77 Example 7 48.4 97 0.59 Example 8 49.6 98 0.40 Example 9 55.9 98 0.52 Comparative Example 1 45.6 97 0.81
[0091] As can be seen from the comparison of the experimental data of Examples 1-3 in Table 1, the gutta-percha points prepared by the present application have good tensile strength and antibacterial properties. As can be seen from the comparison of Example 4 and Example 1, changing the ratio of glutathione to chitosan may result in too high a bending strength of the gutta-percha point, which is prone to leakage. As can be seen from the comparison of Example 5 and Example 1, changing the ratio of zinc acetate in anhydrous ethanol solution to esterified chitosan results in a decrease in bending strength, which cannot tightly fit in the root canal, causing leakage. As can be seen from the comparison of Example 6 and Example 1, using an antibacterial agent that does not contain chitosan has poor dispersibility, and all performance indicators decrease. As can be seen from the comparison of Example 7 and Example 1, using an antibacterial agent that does not contain esterified chitosan results in a decrease in sealing performance. As can be seen from the comparison of Examples 8 and 9 and Example 1, changing the ratio of gallic acid to acrylic acid and the ratio of ceramic powder to allylated gallic acid results in a decrease in bending performance, causing leakage. As can be seen from the comparison of Comparative Example 1 and Example 1, directly using ceramic powder results in poor bending performance and poor anti-leakage performance of the gutta-percha point.
[0092] The above embodiments are only for illustrating the technical concept and characteristics of the present application, and the purpose is to enable those skilled in the art to understand the content of the present application and implement it, and cannot limit the protection scope of the present application. Any equivalent changes or modifications made according to the spirit and essence of the present application should be covered within the protection scope of the present application.
Claims
1. A bioceramic gutta-percha tip, characterized in that: The composition comprises the following raw materials in parts by weight: 10-20 parts of natural rubber, 30-40 parts of antibacterial agent, 8-12 parts of barium sulfate, 8-15 parts of modified ceramic powder, and 0.7-3 parts of plasticizer; The preparation method of the antibacterial agent comprises the following steps: 1) Add glutathione and chitosan to DMSO, then add sulfuric acid solution, react at 70-80°C for 7-8 hours, filter, wash, and dry to obtain esterified chitosan; 2) stirring a 0.05-0.06 mol / L zinc acetate solution in anhydrous ethanol at 40-50° C. for 50-70 minutes, then adding a 0.08-0.09 mol / L sodium hydroxide solution while stirring, and simultaneously adding the esterified chitosan obtained in step 1), stirring at 40-50° C. for 1-2 hours, allowing to stand, filtering, washing, and drying to obtain an antibacterial agent; The mass ratio of glutathione to chitosan in step 1) is (0.2-0.5):1; The mass ratio of the anhydrous ethanol solution of zinc acetate to the esterified chitosan in step 2) is 1:(0.1-0.5); The preparation method of the modified ceramic powder comprises the following steps: (1) Gallic acid and acrylic acid are added to dichloromethane, and then phosphoric acid solution is added, stirred at 70-80°C for 7-8 hours, extracted, concentrated, and dried to obtain allylated gallic acid; (2) adding the ceramic powder and KH570 to ethanol, reacting at 70-80°C for 5-6 hours, then adding the allylated gallic acid and azobisisobutyronitrile obtained in step (1), and continuing the reaction for 1-2 hours to obtain the modified ceramic powder; The mass ratio of gallic acid to acrylic acid in step (1) is 1:(0.5-0.9); The mass ratio of the ceramic powder to the allyl gallic acid is 1:(0.2-0.6).
2. The bioceramic gutta-percha tip according to claim 1, characterized in that: The ceramic powder is nano-scale zirconium dioxide ceramic powder with a particle size of 30-50 nm.
3. The bioceramic gutta-percha tip according to claim 1, characterized in that: The plasticizer is one or more of rosin, beeswax or palm wax.
4. A method for preparing the bioceramic gutta-percha tip according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: refining natural rubber at 80-100°C for 1-2 hours, then adding an antibacterial agent, barium sulfate, modified ceramic powder and a plasticizer, heating to 100-110°C and stirring for 55-65 minutes, then adding the mixture into a mold and cooling it at room temperature to obtain a bioceramic gutta-percha tip.
Citation Information
Patent Citations
Nano-type leaf surface regulating agent capable of improving cadmium tolerance of rice and preparation method thereof
CN113951254A
KR20220094177A